Evaluation of Layer Thickness Dependence of Critical Current Density using Longitudinal Magnetic Field Effect in Superconducting Coated Conductors. (September 2019) - Yonenaka, T; Otabe, E S; Vyatkin, V; Lee, S; Akune, T; Nishizaki, T
Abstract: When the critical current density J c for a superconductor is constant, the critical current I c increases in proportion to the superconducting cross-sectional area. However, in the case of a superconducting coated conductor, when the thickness of the superconducting layer exceeds about 2 μm, there is no further increase in I c . This is because J c decreases due to the structural degradation of the superconducting layer. In this study, J c for samples with superconducting layers of different thicknesses was measured using the longitudinal magnetic field effect in order to investigate the optimum layer thickness for maximizing I c . Differences in the J c characteristics due to the layer thickness appeared more clearly under a longitudinal magnetic field than a transverse magnetic field. This was particularly true at low temperatures, and the optimum layer thickness was found to be approximately 1 μm.